Split or steal? Cooperative behavior when the stakes are large - van den Assem, Martijn J.; van Dolder, Dennie; Thaler, Richard H. (Institute for Operations Research and the Management Sciences, 2011)
We examine cooperative behavior when large sums of money are at stake, using data from the TV game show “Golden Balls”. At the end of each episode, contestants play a variant on the classic Prisoner’s Dilemma for large and widely ranging stakes averaging over $20,000. Cooperation is surprisingly high for amounts that would normally be considered consequential but look tiny in their current context, what we call a “big peanuts” phenomenon. Utilizing the prior interaction among contestants, we find evidence that people have reciprocal preferences. Surprisingly, there is little support for conditional cooperation in our sample. That is, players do not seem to be more likely to cooperate if their opponent might be expected to cooperate. Further, we replicate earlier findings that males are less cooperative than females, but this gender effect reverses for older contestants because men become increasingly cooperative as their age increases.